POLA PERGERAKAN TRANSPORTASI PENDUDUK YANG DITIMBULKAN OLEH KAWASAN PERUMAHAN DI KOTA MEDAN - Parada Afkiki Eko Saputra; Budi Florianta Tarigan (Universitas Quality, 2019)
Medan City as the location chosen in this study, has an area of 265.00 km2 with a population of 2,210,624 people and is increasing every year (Badan Pusat Statistik, 2015). With the increasing population of the city increasing activity and the number of good people traveling well. The city of Medan is currently promoting quite rapid development, a development from now on with the change in New settlements in the region which were built by settlement developers who also increased transportation development. It is very interesting to discuss about regional settlements in the city of Medan, especially in terms of trip generation. The housing area that is the object of research is part of land use in the Medan city area. From the research results, the best model that can be used at this time can be applied in housing location planning, namely the linear multiple regression model on luxury housing types, namely Y1 = 3.373 + 1.569 X1 + 0.139 X4 + 0.456 X6, therefore the findings that can be found are the variables that have an impact on the trip generation from housing. The value of the variable Number of family members (X1) is equal to 1,569 X1, it can be interpreted as increasing the value of the number of people who will increase travel production by 1,569 trips / family / day. The value of the variable number of motorcycle ownership (X4) is 0.139 X4 which means increasing the number of one unit will increase travel production by 0.139 trips / family / day. The value of the variable number of families attending school (X6) is 0.456 X6 which is related to an increase of one person increasing the production of trips that is equal to 0.456 trips / family / day.